2020
DOI: 10.1177/1475472x20954404
|View full text |Cite
|
Sign up to set email alerts
|

On the integration of acoustic phase-gradient metasurfaces in aeronautics

Abstract: Metamaterials might be one of the breakthrough technologies needed from the aeronautic industry to achieve the more and more challenging targets set by the international authorities, especially about noise emissions. In this article, a theoretical link between Transformation Acoustics and Generalized Snell’s Law, two widely used metamaterial models, is demonstrated analytically and applied to case studies. The relevance of the connection in the aeroacoustic field is discussed along with the consequent computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…However, it can be found that most of the present optimizations for the acoustic metamaterial are based on theoretical modeling [ 20 , 21 , 22 ] or finite element simulation [ 23 , 24 ]. Gritsenko and Paoli [ 20 ] had proposed a novel theoretical approach to characterize bubble-based metamaterials based on the findings for a single bubble trapped in circular cavity modeled as a thin clamped plate and further conducted the theoretical optimization of the trapped-bubble-based acoustic metamaterial performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it can be found that most of the present optimizations for the acoustic metamaterial are based on theoretical modeling [ 20 , 21 , 22 ] or finite element simulation [ 23 , 24 ]. Gritsenko and Paoli [ 20 ] had proposed a novel theoretical approach to characterize bubble-based metamaterials based on the findings for a single bubble trapped in circular cavity modeled as a thin clamped plate and further conducted the theoretical optimization of the trapped-bubble-based acoustic metamaterial performance.…”
Section: Introductionmentioning
confidence: 99%
“…The receptance functions of metamaterial beams with various resonator connection architectures were derived by Wei et al [ 21 ] according to the transfer matrix model and further be verified through finite element model results. Palma and Burghignoli [ 22 ] had conducted the theoretical link between two widely used metamaterial models of transformation acoustics and generalized Snell’s Law, and it was exploited to perform an optimal design of phase-graded metasurface acoustic lining of a 2-D duct in presence of flow. Tang et al [ 23 ] had built the finite element model of the perforated honeycomb-corrugation hybrid to analyze its absorption properties and research viscous-thermal energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…Even though this effort had helped so far to achieve remarkable improvements, nowadays, an asymptotic limit is being reached in terms of efficiency. 9 For this reason, new interests have evolved in studying innovative airframe configurations, low-noise technologies based on metamaterials 10,11 and the use of advanced propulsive systems. During the last decades, ideas about the noise shielding obtained by installing the engines on top of the fuselage have been conceived for both conventional and innovative aircraft configurations.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of metamaterials in aeroacoustics has been recently indicated [8,9] and shown in several works [10][11][12][13][14][15][16]. The particular metamaterials class of the phase-gradient metasurfaces (PGMSs), devoted to sound redistribution more than absorption, has been used to significantly change the noise emission directivity of simple 2D rectangular ducts in numerical simulations [17,18], and, while some technological challenges still remain open, possible synergies with standard liners were speculated. An analytic equivalence between a PGMS and a metafluid designed within the Transformation Acoustics framework was developed in [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The particular metamaterials class of the phase-gradient metasurfaces (PGMSs), devoted to sound redistribution more than absorption, has been used to significantly change the noise emission directivity of simple 2D rectangular ducts in numerical simulations [17,18], and, while some technological challenges still remain open, possible synergies with standard liners were speculated. An analytic equivalence between a PGMS and a metafluid designed within the Transformation Acoustics framework was developed in [18,19]. The metafluid model demonstrated to be a computationally efficient method to address the simulation-based optimisation of the metasurface parameters, enlightening also new paths for building PGMS devices still unexplored.…”
Section: Introductionmentioning
confidence: 99%